Corporate Social Responsibility as a Symptom of the Existential Dissatisfaction in Post-Industrial Economy - Maggiolini, Piercarlo; Nanini, Krysnaia (Brazilian Journal of Operations & Production Management, 2010)
The main purpose of the paper is to give an answer to the following question: why has the interest in Corporate Social Responsibility (CSR) literally exploded in the relatively few recent years? After a brief presentation of the different approaches to CSR (focusing on the behaviours or on the aims of the CSE: CSE only as a means to achieving business goals or also as an aim) the paper introduces Malone’s interesting contribution, trying to show how important it is nowadays to put human values at the centre of business and to promote a “market of human values” (where a relevant role has to be played by the Information and Communication Technologies). Starting from this point of view, and basically using Bell’s classical framework concerning post-industrial society, the paper tries to demonstrate that the growing interest in CSR is a very relevant symptom of the existential dissatisfaction with intrinsic features of post-industrial economy and society.